Service Quality and Customer Repurchase Intention of a Local Restaurant in the Central Philippines - Cordova, Maria Thely; Padilla, Nenette; Bual, Joel (Technium Social Sciences Journal, 2024)
Service quality and customers’ repurchase intention are essential in the restaurants’ successful operation. Thus, this measured the service quality of a local restaurant in a highly urbanized city in Central Philippines in responsive/assurance, empathy/equity, reliability, and tangibility relative to the types of services. Likewise, it determined their repurchase intention in customer satisfaction, customer trust, commitment, and perceived value. Using the descriptive design, this was responded by conveniently sampled 157 customers aged 18 years old and above who had actual dining experience in the restaurant from August to October 2023. It employed the adopted service quality instrument and validated and reliability-tested repurchase intention questionnaire. The data were analyzed using mean and standard deviation. Also, this adhered to the Philippine Health Research Ethics Board (PHREB) guidelines. Generally, most were dine-in customers. They rated the quality of service higher than buffet and catering customers. Moreover, empathy, reliability, and tangibility were very high across customer types. Meanwhile, high customer satisfaction and repurchase intentions were evident among dine-in customers. With this, their exceptional dine-in experience highlights the importance of maintaining high standards in the restaurant’s service quality. Hence, consistent service quality and customer-centric approaches are crucially recommended in enhancing customer satisfaction, loyalty, and repurchase intentions across all service types.